Comparative Genomics Evidence That Only Protein Toxins are Tagging Bad Bugs - Georgiades, Kalliopi; Raoult, Didier (Frontiers in Cellular and Infection Microbiology, 2011)
The term toxin was introduced by Roux and Yersin and describes macromolecular substances that, when produced during infection or when introduced parenterally or orally, cause an impairment of physiological functions that lead to disease or to the death of the infected organism. Long after the discovery of toxins, early genetic studies on bacterial virulence demonstrated that removing a certain number of genes from pathogenic bacteria decreases their capacity to infect hosts. Each of the removed factors was therefore referred to as a “virulence factor,” and it was speculated that non-pathogenic bacteria lack such supplementary factors. However, many recent comparative studies demonstrate that the specialization of bacteria to eukaryotic hosts is associated with massive gene loss. We recently demonstrated that the only features that seem to characterize 12 epidemic bacteria are toxin-antitoxin (TA) modules, which are addiction molecules in host bacteria. In this study, we investigated if protein toxins are indeed the only molecules specific to pathogenic bacteria by comparing 14 epidemic bacterial killers (“bad bugs”) with their 14 closest non-epidemic relatives (“controls”). We found protein toxins in significantly more elevated numbers in all of the “bad bugs”. For the first time, statistical principal components analysis, including genome size, GC%, TA modules, restriction enzymes and toxins, revealed that toxins are the only proteins other than TA modules that are correlated with the pathogenic character of bacteria. Moreover, intracellular toxins appear to be more correlated with the pathogenic character of bacteria than secreted toxins. In conclusion, we hypothesize that the only truly identifiable phenomena, witnessing the convergent evolution of the most pathogenic bacteria for humans are the loss of metabolic activities, i.e., the outcome of the loss of regulatory and transcription factors and the presence of protein toxins, alone or coupled as TA modules.